2019
DOI: 10.3390/su11113131
|View full text |Cite
|
Sign up to set email alerts
|

Natural Farming Improves Soil Quality and Alters Microbial Diversity in a Cabbage Field in Japan

Abstract: Natural farming (NF), an environmentally friendly agricultural practice similar to organic farming, was developed in Japan. Unlike conventional farming, little is known about the influence of NF on soil microbial communities, especially the surface soil. We therefore compared the effect of seven years’ conventional practice (CP), conventional practice without chemicals (CF), and NF on soil properties and microbial community structure at two soil depths (0–10, 10–20 cm) in an experimental cabbage field. Both so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 63 publications
3
28
0
Order By: Relevance
“…Conventional farming, in contrast, slightly increased the abundance of xenobiotics biodegradation and metabolism, while organic farming was the lowest. This supported the idea that conventional farming, which relied on synthetic agrochemical usages (i.e., herbicides and NPK fertilizers), provided a toxic environment for the microbes, and xenobiotic-degrading genes were increased as a response (Liao et al, 2019). It also elevated the nitrogen metabolism of the phyllosphere microbes, including glutamine synthetase (K01915) and nitrite reductase (NADH) large subunit (K00362), which were identified as conventional-specific functions by LEfSe.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Conventional farming, in contrast, slightly increased the abundance of xenobiotics biodegradation and metabolism, while organic farming was the lowest. This supported the idea that conventional farming, which relied on synthetic agrochemical usages (i.e., herbicides and NPK fertilizers), provided a toxic environment for the microbes, and xenobiotic-degrading genes were increased as a response (Liao et al, 2019). It also elevated the nitrogen metabolism of the phyllosphere microbes, including glutamine synthetase (K01915) and nitrite reductase (NADH) large subunit (K00362), which were identified as conventional-specific functions by LEfSe.…”
Section: Discussionsupporting
confidence: 52%
“…Co-occurrence network analysis was subsequently performed to compare the structure and complexity of phyllosphere microbial communities in response to farming practices. Network topology assessments showed that organic network had the highest number of edges, density, and connectivity, which might be linked to the strong resilience capabilities of the phyllosphere microbiota under this farm to disturbances or invasion of exogenous microbes ( Mendes et al, 2018 ; Banerjee et al, 2019 ; Liao et al, 2019 ). Moreover, greater complexity and connectivity in the organic network were followed by the number of hub species identified, while unsustainable farming was in contrast.…”
Section: Discussionmentioning
confidence: 96%
“…Root microbiomes host a large variety of bacteria, many of which are associated with the host plant and enhance plant nutrition, stress tolerance or health. Previous studies have focused on soil microbial communities under organically or naturally managed farms (Li F. et al, 2017;Liao et al, 2018Liao et al, , 2019, but a limited number of studies have reported on plantassociated microbes. Elucidating whether farming practices, such as nature farming vs. conventional practices that employ chemical fertilizers, can influence root microbial communities is therefore of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2019) reported that long-term application of chemical fertilizers reduced the richness and diversity of soil microbes. On the other hand, organically managed fields had more positive effects on alpha-diversity parameters than conventionally managed fields (Hartmann et al, 2015;Gu et al, 2017;Liao et al, 2019). Xia et al (2015) reported that the diversity of the endophytic community associated with plants was higher under organic practices than under conventional practices.…”
Section: Root Microbial Community Composition Under Different Farmingmentioning
confidence: 99%
See 1 more Smart Citation